2017
DOI: 10.1177/0194599817731729
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the ETDQ‐7 for Identifying Persons with Eustachian Tube Dysfunction

Abstract: Objective Compare the accuracy of the Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7) in identifying people with Eustachian tube (ET) dysfunction based on symptoms and based on an objective ET function test. Study Design Cross-sectional study. Setting Tertiary referral center. Subjects and Methods 55 subjects with and without symptoms suggestive of ET dysfunction completed the ETDQ-7 questionnaire and had their ET function evaluated by the percentage of middle ear pressure equilibrated after 5 swall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 26 publications
3
55
1
8
Order By: Relevance
“…Receiver operating characteristic (ROC) curve analysis of the ETDQ‐7 identified a cut point total score of ≥14.5 (mean score = ≥2.1) with perfect 100% sensitivity and 100% specificity for diagnosing a patient with ETD . Teixeira et al compared the ETDQ‐7 to objective eustachian tube function tests (the pressure chamber test and the inflation‐deflation test) on a population of control patients and a population of ETD patients, and found that an ETDQ‐7 score >14.5 had higher sensitivity and specificity than the objective tests . However, the ETD population of that study included not only patients with objective signs of ETD (recurrent otitis media, middle ear effusion, need for tympanostomy tubes) but also patients who only had symptoms of aural fullness and pressure, so its findings may be flawed.…”
Section: Discussionmentioning
confidence: 99%
“…Receiver operating characteristic (ROC) curve analysis of the ETDQ‐7 identified a cut point total score of ≥14.5 (mean score = ≥2.1) with perfect 100% sensitivity and 100% specificity for diagnosing a patient with ETD . Teixeira et al compared the ETDQ‐7 to objective eustachian tube function tests (the pressure chamber test and the inflation‐deflation test) on a population of control patients and a population of ETD patients, and found that an ETDQ‐7 score >14.5 had higher sensitivity and specificity than the objective tests . However, the ETD population of that study included not only patients with objective signs of ETD (recurrent otitis media, middle ear effusion, need for tympanostomy tubes) but also patients who only had symptoms of aural fullness and pressure, so its findings may be flawed.…”
Section: Discussionmentioning
confidence: 99%
“…Although largely unmeasured, the assumption has been that the clinical diagnosis reliably translates to the ability of the ET to perform its physiological functions; opening to permit ME pressure equalisation and drainage, and protection of the middle ear. In recent years this link has been questioned, with reports that symptoms and the results of objective tests (tympanometry[ 24 ], tubomanometry[ 25 , 26 ] and middle ear pressure equilibration tests[ 27 ]) were not closely matched. In this study PCA and correlation matrices demonstrated that patient symptoms measured by PROMs, and ET function measured by tests of ET opening for OETD and PETD, appear poorly correlated and vary independently.…”
Section: Discussionmentioning
confidence: 99%
“…While the occurrence of aural symptoms or otic barotrauma on exposure to significant pressure changes is well recognised, baro-challenge-induced OETD is a relatively new term introduced in the 2015 definition of ETD. Previous work has demonstrated that many symptoms associated with ETD do not correlate with underlying ET function measured by objective tests [Jenckel et al, 2014;Liu et al, 2016;Singh et al, 2017;Smith et al, 2018a, b;Teixeira et al, 2018]. However, of all ETD-related symptoms, aural pain on baro-challenge might have been expected to correlate well with obstructive dysfunction, as the symptom appears to be more specific to the condition, being presumed related to inadequate ME pressure equalisation.…”
Section: Discussionmentioning
confidence: 99%